Semiconductor Aspects of Chalcopyrite and its Relevance for Copper Bioleaching: A Review - Rissoni Toledo, Ailton Guilherme [UNESP]; Benedetti, Assis Vicente [UNESP]; Bevilaqua, Denise [UNESP] (Taylor & Francis, 2024)
The demand for copper drives hydrometallurgical innovation amidst high-grade resource depletion. Compared to pyrometallurgy, biohydrometallurgy presents eco-friendly, cost-effective solutions for ore processing. Semiconductor minerals, notably chalcopyrite, which corresponds to the largest source of copper in the earth’s crust, play a critical role. However, chalcopyrite electrochemical behavior in bioleaching remains underexplored. Therefore, this review emphasizes the exploration of irradiation’s influence on biohydrometallurgy, particularly through the utilization of photoreactions or mineral photo corrosion. The focus is on examining the semiconductor properties of chalcopyrite to incorporate it into biohydrometallurgical frameworks and to develop models elucidating the impact of light on the bioleaching of chalcopyrite.
Keywords: chalcopyrite; light; photo-bioleaching; Semiconductor electrochemistry; solution potential